Rights, Wrongs, and Remedies for Inclusive Education for Students with Significant Support Needs: Professional Development, Research, and Policy Reform. (March 2020) - Turnbull, Ann; Turnbull, Rud
The purpose of this article is to respond to the perspectives of Agran and colleagues concerning barriers to general education placement for students with significant support needs from an "on the ground" lens of participation in mediations and due process hearings, as well as conversations with parental inclusion advocates throughout the country. We focus on rights, wrongs, and remedies regarding three key issues: (a) strengthening professional development, (b) conducting and disseminating research on inclusive practices, and (c) reforming policy for stronger implementation and accountability.